Ácido anacárdico como agente de limpeza cavitária em odontologia adesiva - Queiroz, Cristina Maria Fernandes (2015)
The aim of this in vitro study was to evaluate the performance of anacardic acid as a cavity-cleaning agent in adhesive restorations. Three cleaning agents were used: distilled water (DW), chlorhexidine digluconate solution at 2% (CHX) and anacardic acid (AA). Each cleaning agent was used in two strategies adhesive: after acid etching with phosphoric acid with etch&rinse adhesive or prior to the primer application in self-etch adhesive. Scanning electron microscopy (SEM) analysis was performed to evaluate the morphology of dentin substrate when it was exposed to phosphoric acid or anacardic acid, and when exposed to DW, CHX or AA with the two adhesive strategies. Additionally, spectrophotometry analysis was performed (FTIR) to assess the occurrence of chemical interactions between AA and CHX cleaning agents with dentine. The bond strength to dentin was evaluated by microtensile test, in a total of six experimental groups (2 adhesive strategies x 3 cleaning agents). Flat dentin surfaces were prepared in extracted human teeth. After the use of each cleaning agent and the respective adhesive procedure, teeth were incrementally restored with resin composite up to of 5 mm built-up. The specimens were stored in 37ºC distilled water for 24 h, and were sectioned longitudinally in either direction to obtain the specimens in the form of beams with cross-section area of 1 mm2. Each specimen was tensioned until fracture to with 0.5 mm ̸ min speed in a universal testing machine. The fracture mode was observed using a stereoscope at 60x and 10% of the specimens had their surfaces covered with gold and evaluated under SEM. The bond strength values were statistically evaluated using two-way ANOVA with a 5% significance level. The morphological analysis showed that AA is not able to demineralize dentin and does not alter the substrate surface morphology. The resulting dentin morphological pattern was than that caused by phosphoric acid. FTIR analysis showed that there was a chemical interaction between the AA and dentin as well as it was found an interaction between DG and dentin. Concerning the microtensile bond strength results, there was no statistically significant difference between groups (p> 0.05). The highest percentage of failures was mixed fracture in each group. The anacardic acid did not affect the bond strength after 24 h of storage and analysis showing that it can be used as cavity-cleaning agent.